Simultaneous formation of functional leading and lagging strand holoenzyme complexes on a small, defined DNA substrate - Berdis, Anthony J. (The National Academy of Sciences, 1998)
The biochemical characterization of leading and lagging strand DNA synthesis by bacteriophage T4 replication proteins has been addressed utilizing a small, defined primer/template. The ATP hydrolysis activity of 44/62, the clamp loading complex responsible for holoenzyme assembly, was monitored during assembly of both the leading and lagging strand holoenzyme complex. The ATPase activity of 44/62 diminishes once a functional holoenzyme is assembled on both the leading and lagging strand. The assembly of the lagging strand holoenzyme is facilitated by several factors including biotinylated streptavidin blocks at the end of the fork strands, preassembly of the leading strand holoenzyme, and by the presence of the DNA primase with ribonucleoside triphosphates. The resultant minimal replicative complex consists of two holoenzymes and a primase nested on a model replication fork derived from a 62-mer template/34-mer primer/36-mer lagging strand in an apparent 2:2:1:1 ratio of 45 protein:polymerase:primase:forked DNA. The 44/62 protein complex does not remain associated with the complex. The primase alone slowly synthesizes pentaribonucleotides on the forked DNA when the lagging strand contains a nonannealed TTG initiation site with the rate of synthesis greatly stimulated by the addition of the 41 helicase. The addition of deoxy-NTPs to this complex results in leading strand synthesis, but extension of the synthesized RNA primer does not occur. DNA synthesis in both the leading and lagging strand directions is achieved, however, when a 6-mer DNA primer is annealed to the primase recognition site of the forked DNA substrate. A model is presented that describes how leading and lagging strand DNA synthesis might be coordinated as well as the associated molecular interactions of the replicative proteins.